PRINSIP GOOD CORPORATE GOVERNANCE DALAM PEMENUHAN HAK PEMEGANG SAHAM MINORITAS MENURUT UNDANG-UNDANG NOMOR 40 TAHUN 2007 - Sindy Meikasari; Rumawi Rumawi (Yurisprudentia: Jurnal Hukum Ekonomi, 2021)
Limited Liability Company (PT) is very attractive to investors in the business world. In fact, almost all over the world, the rate of establishment of Limited Liability Companies (PT) is increasing. In Indonesia, the establishment of a Limited Liability Company (PT) by foreign and domestic investors cannot be separated from positive legal regulations. Regarding Limited Liability Companies (PT), it is regulated in Law No. 40 of 2007. It can be said that a Limited Liability Company (PT) is one of the pillars of economic development in Indonesia. Limited Liability Company (PT) was chosen as a form of company, because of its ease of management and transfer of shares. In addition, the Limited Liability Company (PT) also has the status of an independent legal entity. In doing so, there are limited responsibilities for shareholders, Directors and Commissioners. There is also protection for shareholders, both majority and minority. Minority shareholders are usually seen as not having full rights. So, there will be many assumptions about the absence of a right for minority shareholders. In fact, these minority shareholders also have several rights.